Alteration in 1,2-diacylglycerol level and its fatty acid composition in hearts during the growth of hamsters - Okumura, K; Yamada, Y; Kondo, J; Hashimoto, H; Ito, T; Ogawa, K (Basic research in cardiology, 1990)
We measured the amount of 1,2-diacylglycerol (DAG) and its fatty acid composition in hamster hearts of various ages because 1,2-DAG has been recognized to be one of the intracellular second messengers. The highest level in 1,2-DAG was detected in 30-day-old hamster hearts. The heart weight increased about 2.5 times between 30 and 90 days of age. Hamster hearts at 90 days of age had 72% of the 1,2-DAG content at 30 days of age. The amount of 1,2-DAG at 240 days of age was a little lower than that in 90-day-old and 160-day-old hamsters, whereas there was no significant increase in heart weight and only a little gain in body weight between 90 and 240 days of age. The analysis of the fatty acid composition of 1,2-DAG showed an increase in the percentage of 18:0 accompanied by a change in the percentages of other fatty acids with the growth of hamsters. The largest amount of arachidonic acid expressed as 20:4 (n-6) was found at 30 days of age. On the other hand, triglyceride, cholesterol, and major phospholipid components of hamster hearts increased in accordance with growth. In particular, the increase in triglyceride content was remarkable, indicating that myocardial lipidosis may be induced by aging. These results demonstrate that 1,2-DAG may be involved in the synthesis of protein during heart growth and that the alteration of its fatty acid composition is related to the growth of hamsters.